Analisis Komparatif Disimiliaritas Parameter Audit Perpajakan dan Audit Komersial - Anugraheni, Bernadetha Desy; Okfitasari, Antin (JURNAL ILMIAH EDUNOMIKA, 2024)
The phenomenon of inaccurate information in the business and financial world is a common thing but has an influence on the presentation of precise and accurate information and can be accounted for the truth to information users. This factor is the background for the need for an examination or audit as a form of follow-up. Audit is an important part and process to ensure transparency, accountability, and regulatory compliance in the business and financial world. Although they have the same activities such as checking documents for data inaccuracies, tax audits and commercial audits have different specific objectives. The research method used is literature review. The data source used is data. Data collection using literature study. The data analysis technique used is descriptive qualitative. There are similarities in the general objectives between tax audits and commercial audits, namely wanting to ensure that the information, data, and information reported is in accordance with the provisions and is accurate, but there are still different parameters in several aspects of tax audits and commercial audits Kata Kunci : audit pajak, audit komerisal, akuntanbilitas informasi, pemeriksaan